Problem-based learning and proprioception - Eberšek, Boris (Cambridge Scholars Publishing, 2018)
Contemporary teaching and learning methods based on cognitive neuroscience deal with such questions as ""How do we think?"" and ""How do we learn?"" or ""How does the human memory work?"". Innovative approaches in this field tackle the subject of human mentality by connecting discoveries from a range of disciplines that shed light on cognitive occurrences and the learning process. Especially over the last decade, one of the key trends in this field has focused on the connection between humans and machines (technologies) and, more concretely, on the link between human and artificial intelligenc.